Needle stick and sharps injuries and factors associated among health care workers in a Malaysian hospital. - Gyanchand Rampal, Lekhraj Rampal; Zakaria, Rosidah; Leong, Whye Sook; Md. Zain, Azhar (EuroJournals., 2010)
Introduction: Needle stick and sharps injuries (NSSIs) have been recognized as one of the occupational hazards among health care workers (HCWs). They increase risk of spread of diseases like HIV, Hepatitis B and Hepatitis C. The objective of this study was to determine the prevalence and factors associated with needle stick and sharps injuries.